Iron nanoparticles on growth and acclimatization of Chrysanthemum morifolium Ramat. cv. "Jimba" in different culture systems - Tung, Hoang Thanh; Hoai Phong, Truong; Le Ha Nguyen, Phan; Nghia, Luong Thien; Ngan, Ha Thi My; Cuong, Do Manh; Bao, Huynh Gia; Luan, Vu Quoc; Hien, Vu Thi; Ba Nam, Nguyen; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2020)
In plant tissue culture, iron nanoparticles (FeNPs) was one of the first types of nano to be used in plants. Previous reports have identified the effect of FeNPs on many different plant species. In this study, FeNPs was used to replace Fe-EDTA in MS (Murashige, Skoog, 1962) medium to assess their effects on growth, chlorophyll (a, b and a+b) accumulation, antioxidant activity of ascorbate peroxidase (APX) and superoxide dismutase (SOD) enzymes, and acclimatization in greenhouse conditions in different culture systems (in vitro solid, in vitro hydroponic and microponic culture). The obtained results show that FeNPs added to MS medium was higher growth, chlorophyll (a, b and a+b) content, antioxidant activity of SOD and APX enzymes than Fe-EDTA in MS medium as control treatment. The effect of FeNPs are differences between culture systems. In vitro solid and microponic culture systems, the optimal concentration is 75 mM FeNPs and in vitro hydroponic culture system is 100 mM FeNPs. The optimal activity of the antioxidant enzyme SOD (35.04 U.mg−1 prot) obtained in the roots of cultured plants in microponic culture system; meanwhile, the optimal activity of the antioxidant enzyme APX (2.11 μmol.min−1.mg−1 prot) obtained in leaves cultivated in solid culture system. The plantlets derived from MS medium added FeNPs were transfered into greenhouse conditions, the microponic cultivated plants supplemented with FeNPs at a concentration of 100 mM gave the highest survival rate (94.67%). The results of this study showed that FeNPs can replace Fe-EDTA salt in MS medium, and iron deficiency in culture media will reduce chlorophyll content.